Detection of Flavonoid Compounds of Daruju Root Extract (Acanthus ilicifolius Linn) using Thin Layer Chromatography and UV-Vis Spectrophotometry - Aden Dhana Rizkita; Ilham Maulana; Sintia Ayu Dewi (Jurnal Sains dan Kesehatan, 2023)
The isolation and detection of flavonoids in the extract of Daruju root has been carried out. extract obtained from maceration modification using 96% ethanol, ethanol extract The extraction result is concentrated with a rotary evaporator and then evaporated above water bath until a thick extract is obtained. The resulting extract was further separated using a separating funnel and diethyl ether and n-butanol as solvents. Then the thick extract was tested for plavonoid preliminaries by reacting the thick extract with H2SO4 and Mg the results obtained were a change in color to yellow, it proved that the extract was positive for plavonoid. After that, TLC was carried out to purify the extract which would later detect plavonoid using a UV-Vis spectrophotometer. TLC results show an Rf value of 0.6-0.8. UV-Vis spectrophotometer results at a wavelength of 200-800 nm give results in fraction A with a maximum wavelength at 291 nm which is suspected to have detected flavonoids.